Indonesia's Inclusive Economic Diplomacy Based on the Pancasila Ideology - Ngurah Wisnu Murthi; Ihsan Taufiq; Emily Yee; Noval; Ninda Ayuk Aktaniensia (Jurnal Pelita Raya, 2025)
Amid the hegemony of economic globalisation, which often reduces development to growth figures, this study lays a strong foundation for the urgency and contribution of Indonesia's inclusive economic diplomacy grounded in the Pancasila ideology, as an effort to respond to global challenges while realising national ideals. This study employs a qualitative approach with a conceptual-normative design integrated with policy analysis and critical discourse analysis. The results confirm that Pancasila-based inclusive economic diplomacy will only be meaningful if Indonesia dares to treat Pancasila as a moral veto against investments, trade, and green schemes that appear profitable in paper but are detrimental in terms of distribution to workers, MSMEs, farmers, indigenous peoples, and disadvantaged regions. Pancasila, as the state ideology, can function as a productive diplomatic resource, not merely a symbolic backdrop. At the same time, the practical policy implications require institutional mechanisms that transform Pancasila into decision-making metrics through indicators of local supply chains, skills transfer, protection of labour rights, environmental restoration, SME access to project contracts, and a framework for negotiations in the G20, ASEAN, BRICS, OECD, and UNFCCC forums that place transitional justice as a global moral obligation.